The Mark of the Cognitive and the Coupling-Constitution Fallacy: A Defense of the Extended Mind Hypothesis - Piredda, Giulia (Frontiers in Psychology, 2017)
Clark and Chalmers (1998) introduced the extended mind hypothesis, according to which some mental states can be realized by non-biological external resources. A lively debate has flourished around this hypothesis, connected with the issues of embodiment, embeddedness, situatedness and enaction (cf. Clark, 2008; Menary, 2010; Shapiro, 2011). Two of the main criticisms addressed to the functionalist version of the extended mind thesis have been the so-called “coupling-constitution fallacy” and the alleged lack of a mark of the cognitive (Adams and Aizawa, 2001, 2005, 2009, 2010a,b). According to Adams and Aizawa, extended cognition is a logical possibility, but is not instantiated in our world. Following this view, they defend a “contingent intracranialism,” based on a specific mark of the cognitive that they propose. In this paper I intend to show that neither criticism is effective against the extended cognition thesis. In particular: the mark of the cognitive proposed by Adams and Aizawa does not secure contingent intracranialism; the coupling-constitution fallacy criticizes extended cognition on precisely the point the theory was intended to defend: namely, that the best way to individuate cognitive systems, given a minimal mark of the cognitive, is to rely on coupling relations between agents and environmental resources.